Harm reduction—a systematic review on effects of alcohol reduction on physical and mental symptoms. (29th June 2016) - Charlet, Katrin; Heinz, Andreas
Abstract: Based on the knowledge that alcohol misuse causes a multitude of diseases and increased mortality, this systematic review examines whether a reduction of the individual alcohol consumption can contribute to a minimization of health risks within a harm reduction approach. In fact, the reviewed 63 studies indicate that interventions aiming at alcohol reduction (including total abstinence as one possible therapeutic aim) indeed resulted in or were associated with positive effects in harmful, hazardous or alcohol‐dependent drinkers. Major benefits were observed for reducing alcohol‐associated injuries, recovery of ventricular heart function in alcoholic cardiomyopathy, blood pressure lowering, normalization of biochemical parameter, body weight reduction, histological improvement in pre‐cirrhotic alcohol‐related liver disease and slowed progression of an already existing alcohol‐attributable liver fibrosis. Furthermore, reduced withdrawal symptoms, prevalence of psychiatric episodes and duration of in‐patient hospital days, improvement of anxiety and depression symptoms, self‐confidence, physical and mental quality of life, fewer alcohol‐related adverse consequences as well as lower psychosocial stress levels and better social functioning can result from reduced alcohol intake. The reviewed literature demonstrated remarkable socioeconomic cost benefits in areas such as the medical health‐care system or workforce productivity. Individuals with heightened vulnerability further benefit significantly from alcohol reduction (e.g. hypertension, hepatitis C, psychiatric co‐morbidities, pregnancy, but also among adolescents and young adults). Concluding, the reviewed studies strongly support and emphasize the importance and benefits of early initial screening for problematic alcohol use followed by brief and other interventions in first contact medical health‐care facilities to reduce alcohol intake. Abstract : This systematic review shows that a reduction of the individual alcohol consumption can contribute to a minimization of various physical and mental health risks in harmful, hazardous or alcohol‐dependent drinkers (together with socioeconomic cost benefits) within a harm reduction approach. Here, individuals with heightened vulnerability further benefit significantly from alcohol reduction (e.g. individuals with hypertension, hepatitis C, psychiatric co‐morbidities, pregnant or breastfeeding women, and also among adolescents and young adults).